Implementation of Brain-Based Learning to Reduce Mathematics Anxiety in the Teaching of Fractions at Primary School - Erni Nurjanah; Asep Supena (PT. Banjarese Pacific Indonesia, 2025)
This research examines the application of the Brain-Based Learning (BBL) model to reduce math anxiety in teaching fractions at the elementary school level. This study used a quantitative approach with a pretest–posttest quasi-experimental control group design involving two fifth-grade classes: one experimental class that received fraction instruction through BBL and one control class that was taught using conventional methods, with 40 students in each group. Mathematics anxiety related to fractions was measured using a modified mathematics anxiety scale for elementary school students, while fraction achievement was evaluated through a valid written test. The results showed that both groups had relatively equivalent initial abilities, supported by normal and homogeneous pretest data and no significant differences in pretest scores. After the intervention, the experimental class showed consistently lower levels of anxiety related to fractions in all dimensions (tests/assessments, classroom learning situations, fraction tasks, and fraction avoidance) and significantly higher post-test scores than the control class, with an average difference of about seven points. The findings show that BBL, which aligns the learning process with the way the brain naturally learns by fostering positive emotions, multisensory experiences, and meaningful social interaction, is effective in improving students' understanding of fractions while simultaneously reducing their math anxiety. This study offers a unique perspective by conducting an experimental trial of BBL as a targeted intervention for math anxiety related to fractions in Indonesian elementary schools and highlighting its potential as a neuroeducation-based pedagogical strategy to foster numeracy and emotional well-being in math learning.